OS7.3 Health-related quality of life (HRQoL) evaluation in the REGOMA trial: a randomized, phase II clinical trial analyzing regorafenib activity in relapsed glioblastoma patients. (6th September 2019) - Lombardi, G; Del Bianco, P; Brandes, A; Eoli, M; Rudà, R; Ibrahim, T; Lolli, I; Pace, A; Daniele, B; Pasqualetti, F; Rizzato, S; Bergo, E; et al.
Abstract: BACKGROUND: REGOMA trial showed that regorafenib (REG) significantly improved OS and PFS in patients (pts) with relapsed GBM with respect to lomustine (LOM). REG showed a different toxicity profile compared to LOM. Here, we report final results of the HRQoL assessment, a secondary end point. MATERIAL AND METHODS: HRQoL was measured using the European Organization for Research and Treatment of Cancer (EORTC) core questionnaire (QLQ-C30) and brain module (QLQ-BN20) administered before any MRI assessments, every 8 weeks (+/- 2 weeks) until disease progression. To evaluate treatment impact on HRQoL, questionnaires at progression were excluded. Mixed-effect linear models were fitted for each of the HRQOL domain to examine the change over progression-free time within and between arms. The models included the time of questionnaire assessment, the treatment group and their interaction, as fixed effects, and a compound symmetry covariance structure for the random effects. Differences of at least 10 points were classified as a clinically meaningful change. To correct for multiple comparisons and to avoid type I error, the level of significance was set at P=0.01 (2-sided). RESULTS: Of 119 randomized pts, 117 partecipated in the HRQoL evaluation, and 114 had a baseline assessment (n=56 REG; n=58 LOM). No statistically significant differences were observed in any generic or cancer specific domain during treatment in the REG and LOM arms, or between the two arms, except for the appetite loss scale which was significantly worse in PTS treated with REG (Global mean 14.7 (SD=28.6) vs 7.6 (SD=16.0); p=0.0081). The rate of pts with a clinically meaningful worsening for appetite loss was not statistically different between the two arms (9 out of 24 and 0 out of 13 in the REG and LOM arm, respectively;p=0.02). CONCLUSION: In the REGOMA trial, HRQoL did not change during regorafenib treatment. Pts treated with regorafenib and lomustine reported no significant difference in HRQoL.